2016
DOI: 10.1002/nop2.53
|View full text |Cite
|
Sign up to set email alerts
|

What factors influence ward nurses’ recognition of and response to patient deterioration? An integrative review of the literature

Abstract: AimIn this integrative review, we aimed to: first, identify and summarize published studies relating to ward nurses' recognition of and response to patient deterioration; second, to critically evaluate studies that described or appraised the practice of ward nurses in recognizing and responding to patient deterioration; and third, identify gaps in the literature for further research.DesignAn integrative review.MethodsThe Cumulative Index to Nursing and Allied Health Literature (CINAHL) Ovid Medline, Informit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 66 publications
3
107
0
8
Order By: Relevance
“…In general, nurses abilities to recognize and respond to patient's deterioration are of great value to reduce AEs, and with EWS‐S, a framework is given, which enables to respond appropriately and promptly when CDET of patients occurs . However, up to our knowledge, little is known about attitudes towards EWS‐S among different groups of health care workers.…”
Section: Discussionmentioning
confidence: 99%
“…In general, nurses abilities to recognize and respond to patient's deterioration are of great value to reduce AEs, and with EWS‐S, a framework is given, which enables to respond appropriately and promptly when CDET of patients occurs . However, up to our knowledge, little is known about attitudes towards EWS‐S among different groups of health care workers.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Confidence is a common theme in studies that have examined novice RNs' ability to learn skills required for safe patient care. [25][26][27][28] However, few studies focus on novice RN confidence and training strategies in the hospital setting. Investigations of hospital training strategies are needed to build the knowledge base for improving novice RN confidence for the application of clinical skills used towards safe patient care.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the interventions (primarily educational) proposed to address the problem of ALF have tended to focus on the behaviours related to patient monitoring and assessment (Liaw et al, ; Smith, Osgood, & Crane, ). In comparison, there is paucity of studies that have reported the actions of staff when they are escalating care and what influences their escalation behaviour (Massey, Chaboyer, & Aitken, ; Massey, Chaboyer, & Anderson, ; Smith & Aitken, ). The results of this documentary analysis reflect the wider body of evidence, with a higher proportion of statements related to monitoring behaviour compared to escalation behaviour.…”
Section: Discussionmentioning
confidence: 99%